Redistribution Methods for Income Equality in the United States - Sung, Jihyeon (Technium Social Sciences Journal, 2024)
Redistribution for income equality is a contentious issue, with advocates citing increased economic stability and skeptics fearing potential negative impacts on economic growth. The United States (U.S.) faces notably high income inequality compared to the Organisation for Economic Co-operation and Development (OECD) average, with wealth concentrated in the top brackets. This paper critically examines the existing U.S. redistribution methods, including the taxation system and welfare programs, highlighting challenges such as the lack of tax progressiveness in top brackets and limited redistribution compared to European counterparts. Based on this overview, the study evaluates alternative redistribution strategies, including wealth and business taxes. The paper compares theory with insights from pilot programs in other countries. Finally, the paper argues for a universal basic income (UBI) set at per-capita welfare spending, positing that this approach can empower individuals to escape poverty traps, enhance productivity, and introduce a choice mechanism for welfare consumption. Ultimately, this research seeks to propose the most effective and feasible income redistribution policies for the U.S. to bridge the income inequality gap.